A New Resilience Taxonomy. Issue 1 (13th September 2016) - Thompson, Marcus A.; Ryan, Michael J.; Slay, Jill; McLucas, Alan C.
Abstract: Since security is an enduring high‐priority consideration for both individuals and communities, many security methodologies have been proposed. Yet none of these methodologies has achieved a lasting impact on the current security and resilience issues faced in modern society. Methodologies use terminology that is inconsistent, overlapping, contradictory, or contains language that is specific to the domains of physical, electronic, and personnel security. Further, the majority of modern terms focus almost exclusively on electronic or cyber security. Consequently, the current set of security terms and definitions provide little assistance to stakeholders when articulating requirements, nor to systems designers when defining system architectures. Current security‐related resilience terminology is similarly confused, with a lack of commonality, domain‐specific language, and terms used synonymously to blur the distinction between security and security‐related resilience. This paper builds on previous work to present a cohesive taxonomy of security‐related resilience that is applicable across the physical, electronic, and personnel domains.